IMPLEMENTASI MANAJEMEN PEMBIAYAAN MURABAHAH KREDIT PEMILIKAN RUMAH PADA BANK BTN SYARIAH KCPS INDRAMAYU - FAUZAN, IBNUDIN IBNU (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2020)
This research was also motivated by the combination of Murabaha and wakalah contracts, and the KPR financing was carried out by wakalah agreements in advance and conducted Murabaha contracts. This research is in the form of qualitative research. The results of this study are the management of KPR financing at Bank BTN Syariah KCPS Indramayu, which follows existing procedures, such as filing financing until the disbursement process and the binding process of collateral through a notary public. Of course, the purpose of the financing is to both benefits both parties, namely the Customer and Developer, as well as Bank BTN Syariah KCPS Indramayu, with the existence of the KPR financing, which can improve people's welfare to own a house. Murabaha and wakalah financing at Bank BTN Syariah KCPS Indramayu is following sharia law, which refers to the proposition of the Qur'an and the hadith as well as the Sharia Board Fatwa No: 04 / DSN-MUI / IV / 2000 concerning Murabahah and Fatwa of the Sharia Council No: 10 / DSN-MUI / IV / 2000 concerning Wakalah.